Exploring rumen fermentation and microbial populations in Dhofari goats fed a chitosan-added diet - Hani M. El-Zaiat; Waleed Al-Marzooqi; Kaadhia Al-Kharousi (Animal Biotechnology)
The use of chitosan (CHI) in ruminant diets is a promising natural modifier for rumen fermentation, capable of modulating both the rumen pattern and microbial activities. The objective of this study was to explore the rumen fermentation and microbial populations in Dhofari goats fed a diet supplemented with CHI. A total of 24 Dhofari lactating goats (body weight, 27.32 ± 1.80 kg) were assigned randomly into three experimental groups (n = 8 ewes/group). Goats were fed a basal diet with either 0 (control), 180 (low), or 360 (high) mg CHI/kg of dietary dry matter (DM) for 45 days. Feeding high CHI linearly increased (p < 0.05) the propionate level and reduced the acetate, butyrate, and total protozoa count (p < 0.05). Ruminal ammonia nitrogen (NH3–N) concentrations and the acetate:propionate ratio decreased linearly when goats were fed CHI (p < 0.05). The abundances of both Spirochetes and Fibrobacteres phyla were reduced (p < 0.05) with both CHI doses relative to the control. Both low and high CHI reduced (p < 0.05) the relative abundances of Butyrivibrio hungatei, Fibrobacter succinogenes, Ruminococcus albus, Ruminococcus flavefaciens, Selenomonas ruminantium and Neocallimastix californiae populations. Adding CHI significantly decreased (p < 0.05) the abundances of Ascomycota, Basidiomycota, and Bacillariophyta phyla compared to the control. Adding CHI to the diet reduces the abundance of fibrolytic-degrading bacteria, however, it increases the amylolytic-degrading bacteria. Application of 360 mg of CHI/kg DM modified the relative populations of ruminal microbes, which could enhance the rumen fermentation patterns in Dhofari goats.